Teachers' Question Types and Students' Speaking Performance in EFL Classroom - Dinda Fadilah; Yetty Zainil (Universitas Negeri Padang, 2020)
Questioning could help students in improving their speaking skills along with critical thinking skills. Thus, this study was aimed to find most asked question type used by teachers and what type of question that could encourage students to speak more in EFL classroom in SMAN Kota Padang. The data were collected from classroom observation and stimulated recall interviews with the teachers. From the data analysis, it was found that LOTS questions were the most asked question. However, HOTS questions were able to encourage students to speak more compared to LOTS questions. From the interview, it was found that students’ could answer longer with the help of stimulus or the questions helped them to relate with daily life surrounding. On the other hand, some active students and their background could affect the questioning activity in classroom. Students with limited knowledge of vocabularies or timid personality found it harder to speak longer so they tend to answer the questions with few keywords only. The finding suggested that question type could encourage students to speak longer under some circumstances.